The Energi Dalam Perspektif Filsafat China - Widia; Fitria Sarnita (Undiksha, 2023)
This article is presented with library research. Literature studies were conducted on books, scientific articles, and references relevant to the concept of energy from a philosophical perspective. Then it is synthesized systematically and in-depth to provide information in the form of meaningful and useful research results. So the results of a literature review on energy from a philosophical perspective are: 1) The universe is composed of particles and energy; 2) All living things on this earth need energy; 3) The human mind is a magnet for generating energy; 4) Energy in humans is divided into two, namely positive and negative energy; 5) The selection of energy that is channeled will determine who the individual is. So it can be said that humans with reason and knowledge have full power over themselves to manage these two potentials.